A Human Factors Approach to Exploring the Experience of Group Trip Planning from the Perspective of Intragroup Interaction. Issue 7 (3rd July 2018) - Zhang, Lanyun; Sun, Xu; Wagner, Christian
ABSTRACT: Previous studies have investigated the experiences and characteristics of holiday decision-making among groups of travelers. This study adds to the knowledge of group trip holiday planning through exploring influential factors (including the individual and group characteristics of travelers), and linking those with their intragroup interactions when planning a group trip. A total of 261 usable questionnaires were collected across two university campuses in the UK and China. The survey employed a retrospective approach, asking participants to recall one of their past group trip planning experiences within the previous 3 months. This study found that intragroup interactions during a group trip planning process are influenced both by tourists' individual factors, such as age, gender, and nationality, and by group characteristics, such as group size, common interest, group type, and group travel style. This study shows that common interest is the most influential factor in terms of its positive impact on group collaboration, feeling of connectedness, strength of preparation, and flexibility and spontaneity during group trip planning process. Further, in general, Chinese groups tend to spend less time on planning their trips before departure, but focus more on the details of the itinerary. Finally, the implications for technologies that are designed to facilitate the group trip planning process, with a view to enhancing the level of group enjoyment, are discussed based on the findings in this study.